An Integrative Arabic Language Learning Model Based on Neurolinguistics and Digital Learning for the Development of Maharah Istima' in 21st Century Islamic Schools - Sovia Fahraini; Muhammad Imam Nawawi; Hisbullah Huda; Nada Ibrahim Alribdi (Assuthur: Jurnal Pendidikan Bahasa Arab, 2026)
Maharah Istima’ is the basis for Arabic language learning, but school practices are still conventional and have not been integrated with neurolinguistics and digital learning. This study develops an integrative model to optimize listening skills in 21st-century Islamic schools. This research is a conceptual study with a qualitative approach through library research. Data are sourced from relevant scientific literature and analyzed using thematic synthesis to formulate a systematic and applicable integrative model. The results of the study indicate that the development of effective Maharah Istima’ must integrate the stimulation of attention, working memory, and emotions as explained in neurolinguistic theory, with interactive multimedia strategies that align with the principles of Richard E. Mayer’s Cognitive Theory of Multimedia Learning, Robert M. Gagné’s systematic learning framework through Gagne’s Nine Events of Instruction, and Alan Baddeley’s Working Memory concept. The formulated integrative model includes the stages of sound recognition, contextual meaning, digital-based interactive reinforcement, and reflective evaluation. This integration enables learning that is more adaptive, interactive, and aligned with students’ cognitive architecture. This research contributes by developing an integrative conceptual framework based on neurolinguistics and digital learning as a practical guide for Arabic language teachers. This model bridges theory and practice and serves as a foundation for further empirical research that is more relevant to 21st-century needs.